Systematic review and co-ordinate based meta-analysis to summarize the utilization of functional brain imaging in conjunction with human models of peripheral and central sensitization - Clarke, Sophie; Rogers, Richard; Wanigasekera, Vishvarani; Fardo, Francesca; Pia, Hossein; Nochi, Zahra; Macian, Nicolas; Leray, Vincent; Finnerup, Nanna Brix; Pickering, Gisèle; Mouraux, André; Truini, Andrea; et al. (European journal of pain, 2024)
BACKGROUND AND OBJECTIVE: Functional magnetic resonance imaging, in conjunction with models of peripheral and/or central sensitization, has been used to assess analgesic efficacy in healthy humans. This review aims to summarize the use of these techniques to characterize brain mechanisms of hyperalgesia/allodynia and to evaluate the efficacy of analgesics. - DATABASES AND DATA TREATMENT: Searches were performed (PubMed-Medline, Cochrane, Web of Science and Clinicaltrials.gov) to identify and review studies. A co-ordinate based meta-analysis (CBMA) was conducted to quantify neural activity that was reported across multiple independent studies in the hyperalgesic condition compared to control, using GingerALE software. - RESULTS: Of 217 publications, 30 studies met the inclusion criteria. They studied nine different models of hyperalgesia/allodynia assessed in the primary (14) or secondary hyperalgesia zone (16). Twenty-three studies focused on neural correlates of hyperalgesic conditions and showed consistent changes in the somatosensory cortex, prefrontal cortices, insular cortex, anterior cingulate cortex, thalamus and brainstem. The CBMA on 12 studies that reported activation coordinates for a contrast comparing the hyperalgesic state to control produced six activation clusters (significant at false discovery rate of 0.05) with more peaks for secondary (17.7) than primary zones (7.3). Seven studies showed modulation of brain activity by analgesics in five of the clusters but also in four additional regions. - CONCLUSIONS: This meta-analysis revealed substantial but incomplete overlap between brain areas related to neural mechanisms of hyperalgesia and those reflecting the efficacy of analgesic drugs. Studies testing in the secondary zone were more sensitive to evaluate analgesic efficacy on central sensitization at brainstem or thalamocortical levels. - SIGNIFICANCE: Experimental pain models that provide a surrogate for features of pathological pain conditions in healthy humans and functional imaging techniques are both highly valuable research tools. This review shows that when used together, they provide a wealth of information about brain activity during pain states and analgesia. These tools are promising candidates to help bridge the gap between animal and human studies, to improve translatability and provide opportunities for identification of new targets for back-translation to animal studies.
Gesehen am 29.08.2024